Anxiogenic-like behavior and deficient attention/working memory in rats expressing the human DISC1 gene - Wang, An-Li; Chao, Owen Y.; Yang, Yi-Mei; Trossbach, Svenja V.; Müller, Christian P.; Korth, Carsten; Huston, Joseph P.; De Souza Silva, Maria Angelica (Pharmacology Biochemistry and Behavior, 2019)
In humans, mutations in the Disrupted-in-schizophrenia 1 (DISC1) gene have been related to psychiatric disorders, including symptoms of abnormal cognitive and emotional behaviors. In our previous studies, overexpression of the human DISC1 gene in rats resulted in schizophrenia-like phenotypes showing deficits in motor learning, impaired cognitive function and dysfunctions of the dopamine system. Here we asked, whether the DISC1 overexpression affects locomotor activity in the open field (OF), anxiety in the elevated plus-maze (PPM), depression-related behavior in the forced swim test (FST), and attention-like/short-term working-memory in the spontaneous alternation behavior (SAB) in the T-maze in transgenic DISC1 (tgDISC1) rats and littermate controls (WT). TgDISC1 rats showed enhanced anxiety behavior in the EPM and an impairment in attention-like/short-term working-memory in the SAB. However, tgDISC1 animals showed no locomotor impairments or depression-like behavior in the OF and FST. These results suggest that DISC1 overexpression leads to higher anxiety level and an attention-like/working-memory deficit. These findings may expand the causal role of DISC1 in its contribution to multiple symptom dimensions of psychiatric disorders.
CRIS-Team WoS Importer:2019-04-30